A Topical Analysis Of Three Northern Hemisphere Accounting Journals’ Output - Murpratomo Murpratomo; Oliver Oliver; Aswinardono Aswinardono; Brown Brown (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2009)
This study investigates publishing characteristics of accepted papers of three prestigious accounting journals - Critical Perspectives on Accounting, Accounting Organizations and Soci-ety, and Contemporary Accounting Research - for the period 2007–2009. It offers insights into the way in which contemporary accounting knowledge has developed, especially in respect to the topics addressed.The results of the topical analysis show that both Critical Perspectives on Accounting and Accounting Organizations and Society enjoy a heavy concentration of historical and profes-sional accounting articles. Critical Perspectives on Accounting also focuses on public sector ac-counting manuscripts, while Accounting Organizations and Society dwells considerably on the topics of environmental accounting and organizational outcomes. The research output of Con-temporary Accounting Research appears entirely technical with a heavy concentration of manu-scripts that cover technical auditing issues, earnings reporting and cost accounting. The clear implication for new accounting journals springing up in the southern hemi-sphere is that there is great scope for an “alternative voice” that not only captures the technicali-ties of Contemporary Accounting Research but also the well worn paths of Critical Perspectives on Accounting and Accounting Organizations and Society in the ‘southern hemisphere’ setting. Keywords: Contemporary accounting output, topical analysis, historical accounting, accounting profession, environmental accounting, auditing, and earnings reporting.